Health and Physical Education, Grades 7-8. Teacher's Guide - Fairfax County Schools, VA.; Fairfax County Schools, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
GRADES OR AGES: Grades 7-8. SUBJECT MATTER: Physical and health education. ORGANIZATION AND PHYSICAL APPEARANCE: The guide is divided into five main sections: 1) organization and administration, 2) content outline and timing, 3) health education program outline, 4) intramural sports, 5) sample units of instruction. Section 5 comprises one half of the guide. The guide is xeroxed and staple-bound with a paper cover. OBJECTIVES AND ACTIVITIES: The sample units list skills to be taught in specific areas of games, gymnastics, track and field, and dance. Earlier sections contain suggestions on methods of organizing the class, student-teacher relations, and scheduling. A short list of program objectives appears in the introduction. INSTRUCTIONAL MATERIALS: Each sample unit includes a list of required equipment and a short list of teacher references. In addition, the guide contains a bibliography of books, magazines, catalogs, films and filmstrips, and other multimedia materials. STUDENT ASSESSMENT: Each sample unit lists several sources for skill and knowledge tests in that area. The guide also contains guidelines and references for diagnostic physical fitness testing. (RT)
Educational level discussed: Grade 7.
Educational level discussed: Grade 8.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Guides; Grade 7.; Grade 8.; Health Education; Physical Education